AgNPs-Azolla Pinnata Extract As Larvicidal Against Aedes Aegypti (Diptera: Culicidae). Issue 1 (December 2020) - Ravi, R.; Ishak, I. H.; Amin, M.F. Mohd; Hamzah, Z; Rasat, M. S. M.; Salam, M.A.
Abstract: The widely used synthetic insecticide in the operation of mosquito control could result in unfavourable impacts to the environment, human health and non-target organism. Considering these issues, environmentally friendly insecticides from plant extract have been used as green alternatives by recent researchers. Unfortunately, the method of using plant extract as insecticide requires a large amount of raw plants. In relation to this problem, the use of nanoparticles that possesses unique characteristics including small size and potential in changing physical, chemical and biological properties of organisms were studied. Nano-synthesized silver particles (AgNPs) from Azolla pinnata extract were thus investigated in this study in order to determine its efficacy as Aedes aegypti larvicide. The present work focuses on extraction of the compounds in Azolla pinnata using soxhlet extraction method. The plant extract was mixed with 1 mM silver nitrate solution and the biosynthesized silver nanoparticles were then being characterized using UV-Vis spectrophotometer. AgNPs particles from Azolla pinnata extract were prepared in six different concentrations and set in plastic cups. Late third instar larvae of Aedes aegypti were being used in all tests. Based on the findings of the experiment, there was no mortality of larvae recorded in control groups after 24 hours of exposure. The lowest mortality recorded was at 10 ppm with only 7.5% mortality, while 95% mortality was recorded for the highest concentration which was 250 ppm. Meanwhile, the LC50 and LC95 obtained at 95% confidence interval after 24 hours of exposure were 121.570 ppm and 369.438 ppm respectively. Further studies should be done to determine the mechanisms of AgNPs in aiding Azolla pinnata as an effective larvicide in the future.